Synthesis and Characterization of Some Dicarboxylato and Salicylato Derivatives of Bismuth(III) Nitrate - Dabas, P.; Saxena, R.; Rastogi, M.K. (Asian Journal of Chemistry, 2010)
Fluorosis, which is a serious public health problem in many areas of the world, is due to excessive intake of fluoride containing food materials. Tea which has been traditionally an important constituent of Indian diet is found to contain fluoride. So this study is to analyse the fluoride content present in different varieties of tea dust and leaves available in the local market of Kanyakumari District (Tamilnadu).